Composition-Tuned Pt-Skinned PtNi Bimetallic Clusters as Highly Efficient Methanol Dehydrogenation Catalysts - Richard Palmer (Chemistry of Materials, 2019)
Platinum is the most active anode and cathode catalyst in next-generation fuel cells using methanol as liquid source of hydrogen. Its catalytic activity can be significantly improved by alloying with 3d metals, although a precise tuning of its surface architecture is still required. Herein, we report the design of a highly active low-temperature (below 0 °C) methanol dehydrogenation anode catalyst with reduced CO poisoning based on ultralow amount of precisely defined PtxNi1–x (x = 0 to 1) bimetallic clusters (BCs) deposited on inert flat oxides by cluster beam deposition. These BCs feature clear composition-dependent atomic arrangements and electronic structures stemming from their nucleation mechanism, which are responsible for a volcano-type activity trend peaking at the Pt0.7Ni0.3 composition. Our calculations reveal that at this composition, a cluster skin of Pt atoms with d-band centers downshifted by subsurface Ni atoms weakens the CO interaction that in turn triggers a significant increase in the methanol dehydrogenation activity.